Emergence of evaluative stance: Tracing primary school children's language development in story writing. Issue 1 (13th September 2015) - Hedeboe, Bodil
Abstract : The goal of this corpus study is to trace developmental language patterns of (L1 and L2) primary school children's stories from Primary three to Primary five. The study focuses on genre-specific, interpersonal language resources chosen by the students to construe an evaluative stance. The L2 student texts are the first results of an ongoing genre-based pedagogic project involving explicit teaching of genre. The L1 student texts represent a control group whose pedagogic background is unknown to the researcher. The study applies analysis of story phases (Rose 2006; Martin and Rose 2008) and the annotation software UAM CORPUS TOOL, based on a systemic functional linguistic framework (Halliday and Matthiessen 2004; O'Donnell 2008). The analysis implies that the students seem to develop resources to construe stories that involve some distinct linguistic choices essential to fulfil the socio-cultural purpose of the story genre.